Mathematical Modeling and Experimental Breakthrough Curves of Carbon Dioxide Adsorption on Metal Organic Framework CPM-5 - Sabouni, Rana (2013)
It is essential to capture carbon dioxide from flue gas because it is considered one of the main causes of global warming. Several materials and different methods have been reported for CO2 capturing including adsorption onto zeolites and porous membranes, as well as absorption in amine solutions. All such methods require high energy input and high cost. A new class of porous materials called Metal Organic Frameworks (MOFs) exhibited excellent performance in extracting carbon dioxide from a gas mixture. In this study, the breakthrough curves for the adsorption of carbon dioxide on CPM-5 (crystalline porous materials) were obtained experimentally and theoretically using a laboratory-scale fixed-bed column at different experimental conditions such as feed flow rate, adsorption temperature, and feed concentration. It was found that the CPM-5 has a dynamic CO2 adsorption capacity of 11.9 wt % (2.7 mmol/g) (corresponding to 8 mL/min, 298 K, and 25% v/v CO2). The tested CPM-5 showed an outstanding adsorption equilibrium capacity (e.g., 2.3 mmol/g (10.2 wt %) at 298 K) compared to other adsorbents, which can be considered as an attractive adsorbent for separation of CO2 from flue gas